Micro-electro discharge machining of nonconductive zirconia ceramic: investigation of MRR and recast layer hardness - Banu, Asfana; Ali, Mohammad Yeakub; Abd. Rahman, Mohamed (Springer London, 2014)
Increasing material removal rate (MRR) and minimizing recast layer hardness are critical issues in machining non-conductive ceramic using micro-electro discharge machining(micro-EDM). This paper presents the analysis of MRR and recast layer hardness of zirconium oxide (ZrO2) due to micro-EDM using EDM-3 dielectric fluid and tungsten tool electrodes. The twomain parts of this research are process development and the analysis of MRR and recast layer hardness. In process development, the appropriate use of assisting electrode (AE), polarity, flushing, feed rate, gap voltage, and tool electrode rotational speed are identified. The better machinability of ZrO2 was found to be with copper adhesive as AE, positive workpiece polarity, 3-μm/s feed rate, and workpiece submerged in dielectric fluid with one-way circulation. Empirical models are developed for the estimation of MRR and recast layer hardness. The optimum parameters for maximum MRR and minimum recast layer hardness are found to be at a 370-rpm rotational speed and at 80-V gap voltage.